{Nutrition knowledge, attitudes, and perceptions of Greek menopausal women.} - Papadima, Evgenia-Ioanna; Vassilakou, Tonia; Grigoriadis, Themos; Boutsiadis, Anastasios; Ivanidou, Sofia; Kalampalikis, Andreas; Michala, Lina (Menopause (New York, N.Y.), 2024)
OBJECTIVE: Nutritional guidelines for postmenopausal women differ. This study aimed to assess postmenopausal women's knowledge, beliefs, and practices regarding nutrition during menopause and their dietary habits. METHODS: This cross-sectional study was conducted in a menopause clinic, and data from 105 women were analyzed. A nutrition knowledge, attitudes, and perceptions (KAP) questionnaire was designed, structured, and piloted before implementation, based on the Hellenic dietary guidelines. International Physical Activity Questionnaire-Greek version, MedDietScore, and Menopause-specific Quality of Life questionnaires were administered. RESULTS: The mean ± SD age of the women was 56.9 ± 4.6 years. The mean ± SD KAP score was 12.2 ± 3.5. Those who lived in rural areas had lower KAP scores than those who lived in urban areas ( P = 0.004). Of all the women, 74.5{%} knew the Mediterranean diet pyramid, whereas 9.8{%} knew the Hellenic dietary guidelines. Women who had read the guidelines showed better knowledge of Mediterranean diet food groups (Pearson, 0.309; P = 0.039). Knowledge of dairy services was correlated with consumption of dairy products ( P = 0.002). Furthermore, 76.4{%} were willing to participate in nutrition education programs. The International Physical Activity Questionnaire score was positively correlated with years of smoking ( P = 0.002). Physical activity correlated with adherence to the Mediterranean diet ( P = 0.044). CONCLUSIONS: The majority of postmenopausal Greek women in this study were unaware of the Hellenic dietary guidelines. In general, women's knowledge of nutrition during menopause was moderate. Greek postmenopausal women are willing to participate in nutrition education programs, which should raise awareness of healthy lifestyles through nutrition, exercise, and smoking cessation.
Keywords: Attitudes; Cross-Sectional Studies; Diet; Exercise; Feeding Behavior; Female; Greece; Health Knowledge; Humans; Mediterranean; menopause; Middle Aged; Nutrition Policy; POSTMENOPAUSE; Practice; psychology; Quality of Life; Rural Population; Surveys and Questionnaires